Comparative Characteristics Of Ultrasound Anatomy Of The Thyroid Gland And Physical Development Of Children In The Second Period Of Childhood (Eurasian Medical Research Periodical, 2024)
At present, an important and long-term task of medicine is to shift the focus from the study of diseases to the promotion of its health, thus the need for detailed information on the baseline health status of the population.